2019
DOI: 10.3390/microorganisms8010022
|View full text |Cite
|
Sign up to set email alerts
|

Identification by MALDI-TOF MS of Sporothrix brasiliensis Isolated from a Subconjunctival Infiltrative Lesion in an Immunocompetent Patient

Abstract: Sporotrichosis is a globally distributed subcutaneous fungal infection caused by dimorphic fungi belonging to the Sporothrix species complex that affects the skin of limbs predominantly, but not exclusively. A rare case of ocular sporotrichosis in an immunocompetent Brazilian patient from the countryside of Rio de Janeiro State is reported. A 68-year-old woman presented with a subconjunctival infiltrative lesion in the right eye with pre-auricular lymphadenopathy of onset 4 months ago that evolved to suppurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
0
11
0
12
Order By: Relevance
“…Based on the information obtained in the present study, and evaluating the information available for identification of other fungal taxonomic group by MALDI-TOF MS [32,54], it is possible to understand that MALDI-TOF limitation in identifying species of the FSSC is mainly because this analytical technique requires a more accurate and larger database for fungal identification.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the information obtained in the present study, and evaluating the information available for identification of other fungal taxonomic group by MALDI-TOF MS [32,54], it is possible to understand that MALDI-TOF limitation in identifying species of the FSSC is mainly because this analytical technique requires a more accurate and larger database for fungal identification.…”
Section: Discussionmentioning
confidence: 97%
“…This effort in the build-up of an in-house database is substantial and worthwhile. Matos and collaborators [54] have further used the same above mentioned in-house database for the identification by MALDI-TOF MS of a Sporothrix brasiliensis strain isolated from a subconjunctival infiltrative lesion in immunocompetent patient. According to the authors, MALDI-TOF MS technique was as good as the partial sequence of genes (calmodulin, beta-tubulin and chitin synthase, for example) for the identification of S. brasiliensis.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one studies (case reports and case series) reported ocular sporotrichosis with involvement of the conjunctiva, representing a total of 56 patients, with a mean age of 33.33 ± 21.81 years (range 3-80 years) (Table 3) [34,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Most cases have been reported in Brazil (44 cases) and Malaysia (8 cases).…”
Section: Conjunctival Sporotrichosismentioning
confidence: 99%
“…The left eye was more commonly affected than the right one (15 vs. 12 cases, respectively), although in 29 cases, the affected eye was not specified. S. schenckii was isolated in 25% of the cases (14 patients) [39][40][41]44,47,[50][51][52][53] followed by S. brasiliensis (5.3%, 3 cases) [26,45]; isolation was not achieved in 4 patients (7.4%) [3,4,7,11], and in 35 (62.5%), the species involved was not determined [12,34,37,38,43,49]. Previous trauma related to conjunctival implantation was not reported in any patient, although contact with cats was reported in 50 patients (89.3%) (Table 3) [26,34,37,38,40,41,[43][44][45][46][47][48][49][50][51][52][53].…”
Section: Conjunctival Sporotrichosismentioning
confidence: 99%
“…An epidemiologic study found that approximately 1.6 million people die from fungal infections in the world each year ( Struyfs et al, 2021a ), and a global increase in sporotrichosis incidence occurs every year, especially in the tropical and subtropical regions ( Chakrabarti et al, 2015 ). Current therapies to treat sporotrichosis are very limited, which mainly include antifungal drugs, photodynamic therapy, thermotherapy, cryotherapy, and surgery, and the effects are still far from satisfactory ( Honse et al, 2010 ; MF Matos et al, 2020 ; Soeiro Sampaio et al, 2020 ). A more efficient treatment for sporotrichosis is greatly desired.…”
Section: Introductionmentioning
confidence: 99%